Independently assessing the representation of midlatitude cyclones in high‐resolution reanalyses using satellite observed winds - Pepler, Acacia S.; Di Luca, Alejandro; Evans, Jason P. (International Journal of Climatology, 2018)
ABSTRACT High‐resolution reanalyses offer the potential to improve our understanding of midlatitude cyclones, particularly smaller‐scale systems and those with complex structures. However, previous studies have demonstrated large variations in the frequency and characteristics of Australian midlatitude cyclones between reanalyses when using their native resolution. In this paper we use satellite observations of winds and rainfall in order to evaluate the ability of the ERA‐Interim, JRA55, MERRA and CFSR reanalyses to reproduce Australian east coast cyclones. The MERRA reanalysis produces a large number of erroneous small‐scale lows without cyclonic wind patterns using a simple pressure‐difference‐based cyclone identification and tracking method. Consequently, we recommend the ERA‐Interim reanalysis when using such methods, or applying more complex tracking methods that are able to compensate for these issues.

Trends and low frequency variability of East Coast Lows in the twentieth century - Ji, Fei; Pepler, Acacia; Browning, Stuart; Evans, Jasona; Di Luca, Alejandro (Journal of Southern Hemisphere Earth System Science, 2018)

Evaluating the representation of Australian East Coast Lows in a regional climate model ensemble - Di Luca, Alejandro; Evans, Jason; Pepler, Acacia; Alexander, Lisa; Argüeso, Daniel (Journal of Southern Hemisphere Earth System Science, 2016)

Resolution Sensitivity of Cyclone Climatology over Eastern Australia Using Six Reanalysis Products* - Di Luca, Alejandro; Evans, Jason P.; Pepler, Acacia; Alexander, Lisa; Argüeso, Daniel (Journal of Climate, 2015)
Abstract The climate of the eastern seaboard of Australia is strongly influenced by the passage of low pressure systems over the adjacent Tasman Sea due to their associated precipitation and their potential to develop into extreme weather events. The aim of this study is to quantify differences in the climatology of east coast lows derived from the use of six global reanalyses. The methodology is explicitly designed to identify differences between reanalyses arising from differences in their horizontal resolution and their structure (type of forecast model, assimilation scheme, and the kind and number of observations assimilated). As a basis for comparison, reanalysis climatologies are compared with an observation-based climatology. Results show that reanalyses, specially high-resolution products, lead to very similar climatologies of the frequency, intensity, duration, and size of east coast lows when using spatially smoothed (about 300-km horizontal grid meshes) mean sea level pressure fields as input data. Moreover, at these coarse horizontal scales, monthly, interannual, and spatial variabilities appear to be very similar across the various reanalyses with a generally stronger agreement between winter events compared with summer ones. Results also show that, when looking at cyclones using reanalysis data at their native resolution (approaching 50-km grid spacing for the most recent products), uncertainties related to the frequency, intensity, and size of lows are very large and it is not clear which reanalysis, if any, gives a better description of cyclones. Further work is needed in order to evaluate the usefulness of the finescale information in modern reanalyses and to better understand the sources of their differences.

Projected changes in east Australian midlatitude cyclones during the 21st century - Pepler, Acacia S.; Di Luca, Alejandro; Ji, Fei; Alexander, Lisa V.; Evans, Jason P.; Sherwood, Steven C. (Geophysical Research Letters, 2016)
Abstract The east coast of Australia is regularly influenced by midlatitude cyclones known as East Coast Lows. These form in a range of synoptic situations and are both a cause of severe weather and an important contributor to water security. This paper presents the first projections of future cyclone activity in this region using a regional climate model ensemble, with the use of a range of cyclone identification methods increasing the robustness of results. While there is considerable uncertainty in projections of cyclone frequency during the warm months, there is a robust agreement on a decreased frequency of cyclones during the winter months, when they are most common in the current climate. However, there is a potential increase in the frequency of cyclones with heavy rainfall and those closest to the coast and accordingly those with potential for severe flooding. , Key Points Winter cyclones are projected to decrease on the Australian east coast Cyclones associated with heavy rainfall may increase in frequency Projections of warm season cyclones remain uncertain

Impact of Identification Method on the Inferred Characteristics and Variability of Australian East Coast Lows - Pepler, Acacia S.; Di Luca, Alejandro; Ji, Fei; Alexander, Lisa V.; Evans, Jason P.; Sherwood, Steven C. (Monthly Weather Review, 2015)
Abstract The Australian east coast low (ECL) is both a major cause of damaging severe weather and an important contributor to rainfall and dam inflow along the east coast, and is of interest to a wide range of groups including catchment managers and emergency services. For this reason, several studies in recent years have developed and interrogated databases of east coast lows using a variety of automated cyclone detection methods and identification criteria. This paper retunes each method so that all yield a similar event frequency within the ECL region, to enable a detailed intercomparison of the similarities, differences, and relative advantages of each method. All methods are shown to have substantial skill at identifying ECL events leading to major impacts or explosive development, but the choice of method significantly affects both the seasonal and interannual variation of detected ECL numbers. This must be taken into consideration in studies on trends or variability in ECLs, with a subcategorization of ECL events by synoptic situation of key importance.

Review of Australian east coast low pressure systems and associated extremes - Dowdy, Andrew J.; Pepler, Acacia; Di Luca, Alejandro; Cavicchia, Leone; Mills, Graham; Evans, Jason P.; Louis, Simon; McInnes, Kathleen L.; Walsh, Kevin (Climate Dynamics, 2019)